In the trail of bird-of-paradise: information design in historical image reproduction techniques - de Barros, Helena (InfoDesign, 2023)
This article proposes to investigate how the reproduction of images impacted the conditions for the dissemination of scientific knowledge, based on strategies of representation and visual communication. As historical techniques of image reproduction, it is understood here the manual engraving of the matrix (i.e., xylography, chalcography and lithography) that preceded the photomechanical processes until the end of the 19th century. As a case study, the research was conducted by visual representations of the bird-of-paradise – an exotic bird, originating from islands in Southeast Asia, inaccessible to Europe at the time – addressing how it makes itself known to a wider audience, through printed images. Questions related to the modes of visual representation and graphic techniques will be addressed as fundamental attributes for understanding the theme, discussing their different languages, characteristics, limitations and potentialities for the domain and acquisition of knowledge mediated by information design.